Social Assistance and Labour Supply - Louis Christofides (Center for Economic Studies and ifo Institute (CESifo), 1999)
The longitudinal, 1988-89, LMAS makes it possible to study the interaction between social assistance and labour supply while allowing for substantial time dependence. Tobit equations for hours worked on and off social assistance, which allow for endoge nous selection of social assistance status, are estimated using FIML. Small, but statistically significant, effects for a social assistance benefit variable are obtained, particularly for females. A claw-back variable is not consistently useful. The wage rate has a consistently negative coefficient in the selection equations and is important in the Tobit equations. The paper attempts to reconcile results in earlier literature.
Keywords: 330